EGFR T790M Mutation Detection in Patients With Non-Small Cell Lung Cancer After First Line EGFR TKI Therapy: Summary of Results in a Three-Year Period and a Comparison of Commercially Available Detection Kits - Eszter Bencze; Krisztina Bogos; Andrea Kohánka; László Báthory-Fülöp; Veronika Sárosi; Erzsébet Csernák; Nóra Bittner; Zsombor Melegh; Erika Tóth (Frontiers Media S.A., 2022)
EGFR mutation in non-small cell lung cancer (NSCLC) offers a potential therapeutic target for tyrosine kinase inhibitor (TKI) therapy. The majority of these cases, however eventually develop therapy resistance, mainly by acquiring EGFR T790M mutation. Recently, third-generation TKIs have been introduced to overcome T790M mutation-related resistance. Cell free circulating tumor DNA (liquid biopsy) has emerged as a valuable alternative method for T790M mutation detection during patient follow up, when a tissue biopsy cannot be obtained for analysis. In this study, we summarized our experience with Super-ARMS EGFR Mutation Detection Kit (AmoyDx) on 401 samples of 242 NSCLC patients in a 3-year period in Hungary, comprising 364 plasma and 37 non-plasma samples. We also compared the performance of two commercially available detection kits, the cobas EGFR Mutation test v2 (Roche) and the Super-ARMS EGFR Mutation Detection Kit (AmoyDx). The same activating EGFR mutation was detected with the AmoyDx kit as in the primary tumor in 45.6% of the samples. T790M mutation was identified in 48.1% of the samples containing activating EGFR mutation. The detection rate of T790M mutation was not dependent on the DNA concentration of the plasma sample and there was no considerable improvement in mutation detection rate after a second, subsequent plasma sample. The concordance of EGFR activating mutation detection was 89% between the two methods, while this was 93% for T790M mutation detection. The AmoyDx kit, however showed an overall higher detection rate of T790M mutation compared to the cobas kit (p = 0.014). T790M mutation was detected at 29.8% of the patients if only plasma samples were available for analysis, while the detection rate was 70.2% in non-plasma samples. If the activating EGFR was detected in the plasma samples, the detection rate of T790M mutation was 42.4%. Although non-plasma samples provided a superior T790M mutation detection rate, we found that liquid biopsy can offer a valuable tool for T790M mutation detection, when a tissue biopsy is not available. Alternatively, a liquid biopsy can be used as a screening test, when re-biopsy should be considered in case of wild-type results.